Pharmacological and bioanalytical aspects of galangin-a concise report - Patel D.K.; Patel K.; Gadewar M.; Tahilyani V. (My University, 2025)
Flavonoids are low molecular weight plant phytoconstituents, widely distributed in the leaves, seeds, bark and flowers of plants. It has various pharmacological activities and protects plants against ultraviolet radiation, pathogens, and herbivores. Most of the beneficial health effects of flavonoids are mainly due to its antioxidant properties. Galangin is a flavonol found in honey, Alpinia officinarum, Helichrysum aureonitens and in propolis. It showed anti-mutagenic, anti-clastogenic, anti-oxidative, radical scavenging, metabolic enzyme modulating activity and effective against certain types of cancers. The present review described the pharmacological activity and bioanalytical aspects of galangin, which may be benificial to the researchers who wants to explore the hidden potential of galangin. © 2012 Asian Pacific Tropical Biomedical Magazine.